Spatiotemporal Analysis and Modeling of Sea Ice Growth Rate in Nella Fjord, Antarctica: Based on Observations During the 36th Chinese National Antarctic Research Expedition in 2020 - Sun, Xiaoyu; He, Yawen; Lv, Tingting; Li, Chunhua; Gao, Yi; Zhao, Fu; Xue, Zhenshan (Frontiers in Environmental Science, 2022)
Obtaining field sea ice data is crucial because it is essential for the validation and improvement of satellite data and numerical models. During the 36th Chinese National Antarctic Research Expedition, seven large-scale long-term field observations were conducted in Nella Fjord, and large amounts of in situ sea ice and snow thickness data were acquired. Then, the influences of snow cover, topography, and air temperature on the sea ice growth rate were examined. On the basis of the relationship between the sea ice growth rate and air temperature, an empirical variable model of sea ice thickness was developed. The results show that sea ice started to freeze in early March, and the peak growth rate was reached in mid-June, with a mean growth rate of 0.62 cm/d. Between mid-June and mid-October, the mean growth rate was 0.36–0.4 cm/d; between mid-October and mid-November, the mean growth rate dropped to 0.15 cm/d. After mid-November, ice growth stopped, and the ice thickness decreased. The growth rate and thickness of sea ice near the shore were generally greater than those closer to the center of the fjord, with differences of 0.25 cm/d in mean growth rate and 7.16 cm in mean thickness. Because of the large exchanges of heat between the atmosphere and the ocean, the sea ice thickness increased rapidly during the early stage of freeze-up. When the air temperature was between −12 and −15 °C, the ice growth rate was between 0.36 and 0.4 cm/d. However, when the ice thickness reached 0.5 m, the sea ice growth rate became less sensitive to air temperature. In addition, we found that the proposed model has a high simulation performance for the growth rate of sea ice. Based on the model, we estimated that growth rates become zero at an air temperature of approximately −4 °C. Our study highlights the inverse relationship between the sea ice growth rate and the snow thickness and the fact that the sea ice thickness is mainly affected by temperature.